Internationalization of the Curriculum in Israeli Colleges - Marantz-Gal, Amit (International Higher Education, 2016)
The internationalization of the curriculum is discussed in the context an Israeli college. Among the goals is to highlight the diversity of students and to assist in mutual understanding and peace-building.